2014
DOI: 10.1021/ja502347d
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Hydroxyl Species Induce Multiple Reaction Pathways for the Partial Oxidation of Allyl Alcohol on Gold

Abstract: Partial oxidation of alcohols is a topic of great interest in the field of gold catalysis. In this work, we provide evidence that the partial oxidation of allyl alcohol to its corresponding aldehyde, acrolein, over oxygen-precovered gold surfaces occurs via multiple reaction pathways. Utilizing temperature-programmed desorption (TPD) with isotopically labeled water and oxygen species, reactive molecular beam scattering, and density functional theory (DFT) calculations, we demonstrate that the reaction mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 85 publications
0
47
0
Order By: Relevance
“…DFT calculations substantiated this reaction pathway, initially proposed on the basis of a number of experimental evidences [2b,f,4]. Actually labeling experiments using [18] O 2 showed no incorporation of the isotopomer in the oxidation products to confirm that dioxygen acts just as hydride scavenger from the AuNPs surface to produce the hydroperoxo species, Au-OOH, that in turn decomposes to hydrogen peroxide by protonolysis [5]. Interestingly the possibility of obtaining stable Au-H intermediate species paved the way to gold catalysts suitable for reduction reactions.…”
Section: Introductionmentioning
confidence: 75%
“…DFT calculations substantiated this reaction pathway, initially proposed on the basis of a number of experimental evidences [2b,f,4]. Actually labeling experiments using [18] O 2 showed no incorporation of the isotopomer in the oxidation products to confirm that dioxygen acts just as hydride scavenger from the AuNPs surface to produce the hydroperoxo species, Au-OOH, that in turn decomposes to hydrogen peroxide by protonolysis [5]. Interestingly the possibility of obtaining stable Au-H intermediate species paved the way to gold catalysts suitable for reduction reactions.…”
Section: Introductionmentioning
confidence: 75%
“…A variety of reaction types, including molecular and dissociative adsorptions, desorptions, and bimolecular and unimolecular reactions, are covered in this set. Most of these reactions have been investigated previously using the NEB method by other researchers . In summary, 43 elementary reactions which consists of nine different metals, one metal oxide, and seven different surface terminations were studied.…”
Section: Methodsmentioning
confidence: 99%
“…based catalysts [121][122][123][124][125]. Moreover, OMMP (from C3H6 + O) will preferentially react to form propanal (from OMMP1) or acetone (from OMMP2) via a 1,2-H shift reaction instead of PO.…”
Section: Reaction Mechanism On Goldmentioning
confidence: 99%
“…Although many studies have indicated that the epoxidation of propylene using molecular oxygen is unlikely [11,30] [24], in which the stripping of the methyl hydrogen of propylene by atomic O to yield allyl was found to be facile, leading to the final product allyl alcohol or acrolein. Allyl alcohol is known to convert to acrolein on O-covered Au (111), and this is why acrolein is the main partial oxidation product captured on gold-based catalysts [121][122][123][124][125]. Moreover, OMMP (from C 3 H 6 + O) will preferentially react to form propanal (from OMMP1) or acetone (from OMMP2) via a 1,2-H shift reaction instead of PO.…”
Section: Reaction Mechanism On Goldmentioning
confidence: 99%